Pengaruh Profitabilitas, Leverage, Pertumbuhan Penjualan, Penghindaran Pajak pada Perusahaan Subindustri Produksi Batubara: pengaruh profitabilitas, leverage, dan pertumbuhan penjualan terhadap penghindaran pajak pada perusahaan sub industri pertambangan coal production yang terdaftar di Bursa Efek Indonesia tahun 2019 - 2023. - yanti, lisma; Agusiady, Ricky; Fitriana (LPPM STIA Lancang Kuning Dumai, 2025)
This study was conducted to analyze the influence of profitability, leverage, and sales growth on tax avoidance in coal production mining sub-industry companies listed on the Indonesia Stock Exchange in 2019 - 2023. The data in this study is secondary data derived from the annual reports of coal mining companies published on the Indonesia Stock Exchange in 2019, 2020, 2021, 2022, and 2023. Considering the relatively small number of populations, the sample determination uses saturated sampling, so the sample used in this study is 34 companies. Data analysis uses the panel data regression method. The results of the study show that the average value of the company's profitability is 0.024111, then the average value of the company's leverage is 0.0461943, for the average value of the company's sales growth is 0.2115858, and as many as 98 financial statements are indicated to be tax avoidance (CETR < 25%). Furthermore, profitability affects tax avoidance. Leverage has no effect on tax avoidance, and sales growth has no effect on tax avoidance. Simultaneously, profitability, leverage, and sales growth have an effect on tax avoidance with an R-Square value of 0.0837 (8.37%). The remaining 91.63% was influenced by other variables that were not studied in this study, such as: company size, corporate social responsibility, capital intensity, audit quality, etc.